PERANCANGAN SISTEM INFORMASI PEMESANAN LAPANGAN OLAHRAGA BULUTANGKIS DAN FUTSAL PADA SARATOGA HALL PAMULANG BERBASIS ANDROID - Aryo Seto, - (2019)
This research was conducted to develop an Android based sports field ordering information system so that field bookings can be carried out along with payment information through the application. Applications made are expected to help users as sports field seekers and owners as providers of sports venues. The method used is the PIECES method and the waterfall method so that the results become an android application that can facilitate users in accessing information about the sports field being ordered. With the Android based ordering information system on this Saratoga Hall Pamulang field. It is expected to facilitate the public in finding information about the sports field.